Pancasila Village Tolerance Character Education Model: A Case Study of SDN 1 Balun Lamongan - Muharromah, Lailatul; Akhwani, Akhwani; Djazilan, Sukron (BASICA Journal of Arts and Science in Primary Education, 2024)
This study examines the model of tolerance character education in Pancasila Village, a case study at SDN I Balun, Lamongan Regency. Balun Village is known as the "Pancasila Village" because of the harmonious diversity of religions and cultures in it. The purpose of this study is to explore and analyze the implementation of tolerance character education and its impact on students. The research uses a qualitative approach with a case study method, through observation, in-depth interviews with teachers, students, and parents, as well as analysis of documents related to the curriculum and school activities. The results of the study show that SDN I Balun has successfully integrated the values of tolerance in the curriculum and daily activities. The program is carried out through interfaith learning, group discussions, and joint activities in the celebration of religious holidays. This has proven to be effective in building mutual respect among students. In addition, support from the community and cooperation between schools and local religious leaders are key factors in the success of this educational model. The tolerance character education model applied at SDN I Balun can be an example for other schools in Indonesia in promoting Pancasila values, especially tolerance from an early age. Systematic implementation and community support are important elements in shaping the character of students who are inclusive and respectful of diversity.